Government procurement and free trade in the Americas - de la Maza, Jorge Claro (INTAL-ITD Buenos AiresAR, 1999)
Looks at internationally accepted public procurement principles; national procurement laws and internationally agreed principles; public procurement methods; open tendering procedures; bid challenge procedures; and, possible key issues in the FTAA.